Painting your odyssey : processing memory through synesthesia - Cheong, Samantha Wen Yi (Nanyang Technological University, 2021)
Painting your Odyssey focuses on the exploration of using multiple senses to attain a deeper and richer engagement with one’s surroundings. This particular exploration will focus on how the phenomenon of Synesthesia allows people to experience the world differently.